Análise das micro e pequenas empresas e produtores do segmento agronegócio participantes do prêmio MPE Brasil no Estado do Paraná - Barboza, José Vinícius Santos (2016)
Micro and Small Enterprises (MSEs) as well as the Rural Enterprise have great relevance in a regional context. The research aimed to analyze the profile of 121 MPE Brazil Award (Competitiveness Award for Micro and Small Enterprises) in the agribusiness category which is represented by 32% companies and 82% rural producers. Through an exploratory analysis was possible to identify a global overview of the criteria and their respective performances in Leadership (45%), Strategies and Plans (33%), Customers (37%), Society (42%), Information and Knowledge (44 %) People (35%), Processes (45%) and Results (3%). After, data mining techniques were used for analysis by groups; the participants were grouped into four clusters due to their similar characteristics, highlighting the Leadership and Processes criteria with the highest average among all of the criteria. Finally, a detailed analysis by criterion of Excellence was carried out as a way to deepen the results and diagnose the main factors that influence the outcome. It was highlighted some critical factors such as the definition of mission and vision, definition of functions, standardization of processes, availability of information, lack of customer satisfaction assessment, control and then the performance in the social sphere by the entrepreneurs. For these critical factors has been proposed an action plan for results improvement. Among the activities are the executions of courses and workshops, development of management tools, dissemination of good practices, among others. It is suggested the support of entities such as the Sebrae (Brazilian Micro and Small Business Support Service), Senar (Brazilian National Rural Learning Service) and universities. The results show that, as in the literature analyzed, both farmers and micro and small businesses have in common the difficulty in management, development of strategies and management practices. At the same time, there is an increased demand for support services